Climate finance and security in fragile and conflict-affected contexts - Charbonneau, Bruno; Savelli, Adam (2022)
In this article (aimed at staff within the Canadian Governmnet’s Global Affairs Department, Bruno Charbonneau and Adam Savelli (CGIAR FOCUS Climate Security) take stock of how future research can help boost the peacebuilding potential of climate finance in fragile and conflict-affected contexts. Four research questions are developed and linked with objectives to achieve practical outcomes in the climate security finance space.